The infiltrating ability of abdominal wall endometriosis is associated with ectopic endometrial glandular activity - Xiao Zhang; Ying-Ying He; Nan Jiang; Zhi-Gang Sun; Feng Yan; ? Cidanyangzong; Fang Long; Fang-Xin Shi; Xiao-Guang Xu; Zhen Xiao (IMR Press, 2021)
Introduction: The infiltration pattern of endometriosis is one of the most important pathophysiological features of this lesion. Recent studies indicate the infiltrating nature of endometriosis is associated with a lesion's genetic characteristics. However, related research regarding abdominal wall endometriosis (AWE) is limited. The aim of this study is to investigate whether AWE lesions with different infiltrating depth have different clinical and pathological features. Material and methods: A retrospective review of all cases of surgically excised AWE from 2001 to 2018 was performed from the records at Dalian Medical University and its affiliated hospitals. Descriptive data were collected and analyzed. Hematoxylin-eosin stained (H&E) slides were re-evaluated by pathologists for the density of ectopic endometrial glands (DOG). Results: Ninety-one cases were included in this study. Cases were divided into three types according to the depth of infiltration of the lesion: the fascia type (38 cases), the muscle type (40 cases) and the peritonieum type (13 cases). The primary analysis showed that mass size (P = 0.009), serum CA125 levels (P = 0.04) and operation time (P = 0.02) were significantly different among the three groups. Analysis showed that the diameter of the lesion was positively correlated with the infiltrating depth of the lesion, as well as the level of serum CA125 and the operation time. Even for lesions larger than 3 cm, serum CA125 levels and operation time still showed positive correlation with the lesion diameter (P = 0.02 and P < 0.01, respectively). Further histological research indicated that ectopic endometrial glands in deep lesions were more active and had higher density compared to masses in the superficial layers. Conclusion: This study suggests the three types of AWEs have different clinical and pathological features. When a lesion infiltrates deep into the abdominal wall, it has a larger size, is associated with increased serum CA125 levels, and needs longer time for surgical excision. The different infiltrating ability of AWEs is associated with different activities of ectopic endometrial glands.